PENDAFTARAN TANAH SISTEMATIK BERBASIS KEPASTIAN HUKUM DI DESA SUKAMULYA KECAMATAN CIKEMBAR: Systematic Land Registration Based On Legal Certainty In Sukamulya Village, Cikembar District - Putri Valery Christy; Pandamdari, Endang (Faculty of Law, Universitas Trisakti, 2025)
Since the enactment of Ministerial Regulation ATR/BPN No. 6 of 2018, the government has implemented the Complete Systematic Land Registration (CSLR) to accelerate land registration across Indonesia, aiming to register all lands nationwide. However, its implementation faces many challenges, including in Sukamulya Village, Cikembar District. The main issue addressed is describing how the legal certainty-based systematic land registration is carried out in Sukamulya Village, Cikembar District. The author uses a normative juridical research method with a descriptive-analytical approach, utilizing secondary data supported by primary data, analyzed qualitatively. The study reveals obstacles in socialization and land measurement, highlighting the importance of thorough preparation, planning, socialization, and active participation of the CSLR Adjudication Committee and local community to ensure orderly land registration. Additionally, effective communication between the community and village officials during measurement is crucial to ensure accurate land boundaries.